Studi Genealogis atas Tradisi Tumbilatohe di Gorontalo: Sebuah Analisis Foucauldian - Busura, Mohamad Rifaldi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The Tumbilatohe tradition, the practice of lighting lamps ahead of Eid al-Fitr, is mainstreamly narrated as an "authentic" and original tradition belonging to the Muslim community of Gorontalo. However, this claim of originality reduces historical complexity and ignores the Islamization process, which was fraught with power-relations, especially from the Sultanate of Ternate since the 16th century. The existence of identical traditions in surrounding areas, such as Monuntul in Bolaang Mongondow and Ela-Ela in Ternate, further challenges the assumption of the local tradition's purity. This paper seeks to dismantle the hegemonic narrative regarding Tumbilatohe through a synchronic and diachronic historical review, grounded in Michel Foucault's genealogical theoretical framework. Instead of taking this tradition for granted as a neutral manifestation of the integration between Islam and local culture, this study traces the historical roots of Tumbilatohe to uncover the power relations operating behind its formation and transformation. The analysis results indicate that the dynamics of Islamic values within Tumbilatohe are not static, but rather a contested terrain between Islam and localities. Through a genealogy, this paper offers an alternative to deconstructing the reification of a tradition now vulnerable to mere festival and tourism. This research provides a theoretical contribution to the discourse of Islamic philosophy and cultural studies in Indonesia by asserting that tradition is always intertwined with power relations, while simultaneously encouraging philosophical reflection so that society can re-internalise the wisdom embedded within the practice.